STOCK PRICE DYNAMICS OF PALM OIL PLANTATION FIRMS: INSIGHTS FROM CURRENT RATIO, RETURN ON ASSET AND FIRM SIZE - Dewi Maya Sari; Mislinawati; Hilmi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This study aims to analyze the effect of current ratio, return on asset and firm size on the stock price. The data in this study uses secondary data in the form of financial statements that meet the criteria so that 70 observation of companies were obtained. Data was analyzed using the Multiple Regression Analysis method. The results show that current ratio, return on asset, and firm size postive affect changes in stock prices. The implications of this study are that companies need to manage working capital effectively to ensure adequate liquidity, consider stable or increased dividend policies to attract more investors, and pursue acquisition or expansion opportunities to increase the size of the company, which can overall have a positive impact on market perceptions and stock prices.